The toothpaste millionaire - Merrill, Jean.; Palmer, Jan; Bank Street College of Education (Boston : Houghton Mifflin, 1972)
A young girl describes how her school friend made over a million dollars by creating and marketing a cheaper and better toothpaste.
Wilson's Children
Elem. School Library Collection
School Library Media Quarterly (A.A.A.L.)
6.1
3-6
Keywords: Business enterprises -- Fiction; Entrepreneurship -- Fiction